The Antioxidant PAPLAL Protects against Allergic Contact Dermatitis in Experimental Models - Shuichi Shibuya; Kenji Watanabe; Takahiko Shimizu (MDPI AG, 2024)
PAPLAL, a mixture of platinum (nPt) and palladium (nPd) nanoparticles, is widely used as a topical agent because of its strong antioxidant activity. Allergic contact dermatitis (ACD) is one of the most common occupational skin diseases worldwide. However, the role of oxidative stress in ACD remains unclear. In the present study, we investigated the protective effects of topical PAPLAL treatment on 2,4-dinitrofluorobenzene (DNFB)-induced ACD. DNFB treatment increased 8-isoprostane content; upregulated Xdh, Nox2, and Nox4, pro-oxidant genes; and downregulated Sod1, an antioxidant gene, indicating oxidative damage in the ear skin. PAPLAL therapy significantly reduced ear thickness associated with the downregulation of inflammatory cytokine-related genes. PAPLAL also significantly increased the expression of the stress-response-related genes Ahr and Nrf2, as well as their target genes, but failed to alter the expression of redox-related genes. Furthermore, Sod1 loss worsened ACD pathologies in the ear. These results strongly suggest that PAPLAL protects against ACD through its antioxidant activity and activation of the AHR and NRF2 axes. The antioxidant PAPLAL can be used as a novel topical therapy for ACD that targets oxidative stress.